2010
DOI: 10.1093/bja/aeq212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of capsazepine, a transient receptor potential vanilloid type 1 antagonist, on morphine-induced antinociception, tolerance, and dependence in mice

Abstract: Our results suggest that TRPV1 antagonists can be used adjunctively to morphine treatment because they strengthen morphine antinociception and prevent the development of tolerance, and also physical dependence, on morphine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Moreover, upregulation of TRPV1 in the dorsal root ganglion, spinal cord, and sciatic nerve through mitogen-activated protein kinase pathways after chronic morphine treatment contributed to morphine tolerance in rats (Chen et al, 2008). Recently, we reported that blocking TRPV1 with a TRPV1 antagonist, capsazepine, attenuated morphine tolerance and withdrawal symptoms in mice (Nguyen et al, 2010). Taken together, these data imply that TRPV1 may be a molecular target in morphine reward.…”
Section: Introductionmentioning
confidence: 77%
“…Moreover, upregulation of TRPV1 in the dorsal root ganglion, spinal cord, and sciatic nerve through mitogen-activated protein kinase pathways after chronic morphine treatment contributed to morphine tolerance in rats (Chen et al, 2008). Recently, we reported that blocking TRPV1 with a TRPV1 antagonist, capsazepine, attenuated morphine tolerance and withdrawal symptoms in mice (Nguyen et al, 2010). Taken together, these data imply that TRPV1 may be a molecular target in morphine reward.…”
Section: Introductionmentioning
confidence: 77%
“…23 In accordance with the results of previous studies, a recent report indicated blocking TRPV1 receptors with capsazepine (2.5 mg kg -1 ) inhibited morphine tolerance induced by five days of morphine treatment. 24 The results of these studies suggest that sustained opioid exposure also enhances TRPV1 receptor function in the periphery and plays an additional and essential role in sustained morphine induced thermal and tactile hypersensitivity.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, our data first demonstrated that TRPV1 antagonists significantly reduced withdrawal symptoms in morphine-dependent mice. 24 …”
Section: Introductionmentioning
confidence: 99%
“…Their therapeutic potential is being explored in inflammatory [5,6], cardiovascular [7,8], neurodegenerative [9,10], neoplasic diseases [11,12], as well as other disorders [13,14]. The presence of the 4-hydroxy-3-methoxy phenyl residue allows them to specifically interact with sensory neurons, and from this point of view, capsaicin has been used to treat peripheral painful conditions and neuropathies [10,15,16]. It was shown that curcumin regulates the classical and the alternative pathway of nervous system, being used in the treatment of Alzheimer, multiple sclerosis and dementia [9,10,17].…”
Section: Introductionmentioning
confidence: 99%